The Effect of Brand Image and Service Quality on Purchasing Decisions at Indomaret Ahmad Yani Manna South Bengkulu - Ando Alvarez; Sri Handayani; Rina Trisna Yanti (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2023)
The purpose of this study was to determine the effect of brand image and service quality on purchasing decisions at Indomaret Ahmad Yani Manna South Bengkulu.The sample in this study were 75 consumers who shopped for Bimoli oil at Indomaret Ahmad Yani Manna South Bengkulu. Data collection using a questionnaire and the method of analysis used is multiple linear regression, determination test and hypothesis testing.The calculation results from the calculation of the multiple linear regression equation can be seen that X1 (brand image) and X2 (service quality) have an influence on purchasing decisions (Y), with the results of the regression test: Y = 12.881 + 0.291X1 + 0.420 X2 + 4.399 (e) . Brand image has a significant influence on purchasing decisions at Indomaret Ahmad Yani Manna Bengkulu Selatan. This is evidenced by the results of partial hypothesis testing (t test) that a significant value of 0.000 is less than 0.05 and tcount is greater than ttable (3.917> 1.666). This means that if the brand image increases, the purchasing decision will also increase. Service quality has a significant influence on purchasing decisions at Indomaret Ahmad Yani Manna South Bengkulu. This is evidenced by the results of partial hypothesis testing (t test) that a significant value of 0.000 is less than 0.05 and tcount is greater than ttable (4.061 > 1.666). This means that if organizational commitment increases, purchasing decisions will also increase. Brand image and service quality have a significant influence together on customer purchasing decisions at Indomaret Ahmad Yani Manna South Bengkulu. This is evidenced by the results of simultaneous hypothesis testing (test f) that a significant value of 0.000 is less than 0.05 and Fcount > Ftable (21.361 > 3.12). The value of the coefficient of determination is 0.372. This means that X1 (brand image) and X2 (service quality) have a contribution to the purchase decision (Y) of 37.2% while the remaining 62.8% is influenced by other variables not examined in this study..